From GLP-1 Agonism to Triple-Receptor Therapy. Narrative Review of Semaglutide, Tirzepatide, and Retatrutide in Obesity Management. - Darmoń, Jerzy; Makowska, Joanna; Domańska, Karolina; Piegza, Natalia; Sieczka, Anna; Windyga, Maria; Darmoń, Krzysztof Paweł; Papuga, Aleksandra; Hejduk, Makary (Quality in Sport, 2026)
Background: Obesity is a chronic multifactorial disease that affects a growing proportion of the global population. According to the WHO, obesity is now a global concern. From 1990 to 2022, the prevalence of obesity among minors increased from 2% to 8%, and among adults, it rose from 7% to 16%. The growing global prevalence of obesity has intensified the need for pharmacological therapies. Aim: This narrative review presents the clinical efficacy, metabolic effects, and safety profiles of semaglutide, tirzepatide, and retatrutide, with particular emphasis on their underlying mechanisms of action. Materials and Methods: A narrative review was conducted based on key randomised controlled trials, including the STEP, SURMOUNT, and phase II retatrutide programs. Data on weight reduction, metabolic parameters, and adverse events were extracted and analysed. Mechanistic insights were integrated to interpret differences in clinical outcomes. Results: All three therapies produced significant weight reduction and metabolic improvements, with efficacy increasing in relation to the number of targeted receptors. Semaglutide resulted in a weight loss of up to 16.0%, tirzepatide achieved a reduction of 20.9%, and retatrutide demonstrated the highest efficacy, with a weight loss of 24.2%. All agents were associated with improvements in cardiac, glycemic, and lipid profiles. Gastrointestinal adverse events were frequent and dose-dependent, resulting in higher discontinuation rates at higher doses. Conclusions: Incretin agonists represent a significant advancement in obesity pharmacotherapy, with multi-receptor targeting translating into superior metabolic outcomes. Retatrutide demonstrates the highest potential efficacy among studied agents, although further phase III data are required. These findings support the concept that obesity is a chronic disease that requires long-term treatment and highlight the growing role of mechanism-based pharmacotherapy in its management.